Women managers in meetings - Ways of expressing power - Chefneux Gabriela (Bulletin of Transilvania University, 2015)
Power, a widely studied concept, constructs identities, behaviour, knowledge and discourse. Operating through language, hegemony is taken for granted and the discourses it creates become the norms in institutions. Power has been analysed in a variety of organisations – legal, educational, medical and economical. This paper uses the data transcribed from a meeting held in a medium-sized Romanian company that sells building materials, with the aim of identifying the ways in which the woman manager running the company expresses power.